The Justification of Identity Elimination in Martin-Löf's Type Theory. - Klev, Ansten (Topoi: An International Review of Philosophy, 2019)
On the basis of Martin-Löf's meaning explanations for his type theory a detailed justification is offered of the rule of identity elimination. Brief discussions are thereafter offered of how the univalence axiom fares with respect to these meaning explanations and of some recent work on identity in type theory by Ladyman and Presnell.